A New, Eco-Friendly Method for Iodination of Activated Arenes - R. Sathiyapriya; R. Joel Karunakaran (E-Journal of Chemistry)
An effective, eco-friendly method for iodination of arenes is presented. The reaction of activated aromatics with a mixture of sodium iodate and sodium sulphite in the presence of hydrochloric acid gives mono iodoarenes in high yields.